La aplicación de los arts. 1969° y 1970° del código civil peruano sobre indemnización y el principio de igualdad - García Cruzate, Eduardo Daniel (2014)
National sources, rules, doctrine and jurisprudence both nationally and internationally on the correct application of the Arts are reviewed. 1969 ° and 1970 °CC. On compensation and the right to equality contained in them and the principle of equality in the Courts of Justice of Peru. There is little uniformity in the sentences of the various Courts of Justice of Peru and different opinions in both national and international doctrine in relation to the implementation of the courts in relation to the application of the rule in question. In the same vein, and as a basis for this is because establishing a uniform, bounded discretion in sentencing to have a more consistent approach and application in current standards and therefore do not violate the principle of equality protected by our legislation and supranational legislation and by virtue of it having a better right to equality in our constitutional and democratic state